Photonic bandgaps engineering in double graded hyperbolic, exponential and linear index materials embedded one-dimensional photonic crystals - Singh B.K.; Bijalwan A.; Pandey P.C.; Rastogi V. (My University, 2025)
We present the structuring of different double graded-index materials in the form of one-dimensional (1D) photonic crystals(PCs)for highly efficient light trapping and controlling photonic devices in terms of tuned and controlled photonic bandgap (PBG) performances. Considered 1D graded photonic crystal (GPC)structures are stacked of hyperbolic, exponential, and linear double graded index layers. In the graded index layers, the refractive indices vary in hyperbolic, exponential, and linear fashions as a function of the layer thickness. These configurations show that the operating frequencies and the number of PBGs can be tuned by controlling layer thickness, grading profiles, and grading parameters of the constituted graded layers. The changes in the grading profiles of the graded layers modulate the operation frequencies and also the number of PBGs. We also found that the operating frequencies and bandwidth of PBGs can be tuned by changing the values of initial and final refractive indices of the graded layer. Therefore, the desirable PBG regions and bandwidths can be achieved and controlled by selecting appropriate parameters of the systems. Results can be implemented to design tunable reflectors, multi-channel filters, sensors, and optical detectors. Also, this work may provide an understanding of the effect of different double graded-index materials on PBG characteristics in the GPCs. © 2019 IOP Publishing Ltd.